Cryptogenic Ischemic Stroke in Migraine: Role of Patent Foramen Ovale - Gollion, Cédric; Lerebours, Fleur; Barbieux-Guillot, Marianne; Fabry, Vincent; Larrue, Vincent (Frontiers in Pain Research, 2022)
Introduction Migraine with aura (MWA) has been associated with cryptogenic ischemic stroke (CIS) after adjustment for the presence of a patent foramen ovale (PFO) assessed by a transcranial Doppler. This study aimed at evaluating the association of MWA with causal PFO assessed by Transesophageal echocardiography (TEE) in CIS. Methods Patients aged 18–54 years consecutively treated for first acute ischemic stroke in a university hospital stroke unit, between January 2017 and December 2019, were included in this cross-sectional study. Associations between migraine subtypes and PFO were tested for all PFO, possibly causal PFO (PFO with large shunt and/or atrial septal aneurysm [ASA]), and the probably causal PFO subset (large shunt and/or ASA, plus risk of paradoxical embolism [RoPE] score ≥ 7). We adjusted the association between migraine subtypes and possibly causal PFO, which included the probably causal subset for age, sex, large artery atherosclerosis, and small vessel disease. Results A total of two hundred and two patients with CIS were included, of whom 42/202 (20%) had MWA, 32/202 (15%) had migraine without aura, and 128/202 (63%) had no migraine. MWA was associated with possibly causal PFO (OR = 4.0, 95%CI [1.78–9.3], P < 0.001) and with probably causal PFO (OR = 5.4, 95%CI [2.37–13], P < 0.001). In a multinomial logistic regression analysis, MWA remained associated with possibly causal PFO (OR = 3.24, 95% CI [1.45–7.2], P = 0.004). Conclusion In a young adult population with CIS, MWA was strongly associated with possibly causal PFO, i.e., with a large shunt or combined with an interatrial septal aneurysm.